Design And Development Of A Tensile Split Hopkinson Gas Gun - Mustaffa Kamal, Muzhaffar (Universiti Sains Malaysia, 2018)
This is a project of Design and Development of the Split Hopkinson Tensile Bar Gas Gun apparatus to launch a striker up to designed velocity to perform tensile strain test to specimen at strain rate of 100/s to 1000/s. The gas gun consists of a barrel, striker, incident bar, pressure tank, valve components and pressure regulator. The objective of this project is to demonstrate the functionality of the gas gun by performing tests with different pressure. The performance of this Gas gun was tested by launching the striker 5 times with the same air pressure stored in the air pressure tank. Then, the procedure is repeated using higher pressure in the pressure tank and data are recorded. The result is that the gas gun is capable to launch the striker up to 13 m/s with 7 bar of air pressure by theoretically producing strain rate of 866.5/s to specimen made from DP6600.